1993
DOI: 10.1038/clpt.1993.131
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular interaction between caffeine and nicotine in humans

Abstract: In a placebo-controlled, double-blind randomized design, we investigated the cardiovascular interaction between caffeine (250 mg intravenously) and nicotine (4 mg chewing gum) in 10 healthy volunteers, both under baseline conditions and during physical and mental stress (standing up and mental arithmetic). Caffeine alone induced a significant increase in blood pressure associated with a decrease in heart rate, whereas nicotine alone increased both blood pressure and heart rate. The combination of caffeine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
1
14
1
Order By: Relevance
“…On the contrary, caffeine increased both blood pressure and FBF-effects that can be largely attributed to caffeine-induced release of plasma catecholamines (27). The increase in FBF with caffeine is somewhat unexpected, as earlier studies reported no effects of caffeine on FBF (27,28). Mental stress experienced during the tests might explain this observation because caffeine is known to magnify vasodilator responses induced by mental stress (28,29).…”
contrasting
confidence: 38%
See 1 more Smart Citation
“…On the contrary, caffeine increased both blood pressure and FBF-effects that can be largely attributed to caffeine-induced release of plasma catecholamines (27). The increase in FBF with caffeine is somewhat unexpected, as earlier studies reported no effects of caffeine on FBF (27,28). Mental stress experienced during the tests might explain this observation because caffeine is known to magnify vasodilator responses induced by mental stress (28,29).…”
contrasting
confidence: 38%
“…The increase in FBF with caffeine is somewhat unexpected, as earlier studies reported no effects of caffeine on FBF (27,28). Mental stress experienced during the tests might explain this observation because caffeine is known to magnify vasodilator responses induced by mental stress (28,29).…”
mentioning
confidence: 45%
“…46,47 This study provided little evidence that the effects of nicotine are influenced by concurrent caffeine (with the exception of working memory accuracy as noted above) and is consistent with other studies examining the combination of these drugs in nonsmoking, moderatecaffeine-consuming individuals. 21,22 This observation may suggest that the coadministration of tobacco and caffeine-containing beverages reflects a behavioral rather than pharmacological mechanism. Sensory characteristics associated with common nicotine and caffeine vehicles (ie, cigarettes, coffee) can influence self-administration.…”
Section: Discussionmentioning
confidence: 93%
“…19,20 Accordingly, there are several reports of the combined effects of nicotine and caffeine in nonnicotine users (N = 10). 21,22 However, these small-sample studies may have been underpowered. Thus, their failure to report an enhanced effect of the nicotine/caffeine combination, relative to either drug alone, may reflect a Type II error.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Specifically, in empirical studies, nicotine administration decreased body weight in humans and rats (Grunberg, 1982;Winders & Grunberg, 1989), decreased aggression in humans (Cherek, 1981;Cherek et aI., 1991) and in rats (Silvennan, 1971;ScheufeJe, 1997), and altered biochemical and behavioral responses to stress in rats (Benwell & Balfour, 1982;Cam & Bassett, 1983;1984;Sharp, Beyer, Levine, Morley, & McAllen. 1987;Peck, Dilsaver, & McGee, 1991;Acri, 1992Acri, , 1994Takada, Thara, Vrano, & Takada, 1995) and in humans (MacDougall, Musante, Castillo, & Acevedo, 1988;Gilbert, Robinson, Chamberlin, & Spielberger, 1989;Pomerleau & Pomerleau, 1990;Levin, Rose, Behm, & Caskey, 1991;Smits, Temme, & Thien, 1993).…”
Section: ) Effects Of Nicotinementioning
confidence: 99%